Mucinous tumor of low malignant potential ("borderline" or "atypical proliferative" tumor) of the ovary: A study of 171 cases with the assessment of intraepithelial carcinoma and microinvasion - Khunamornpong S. (2014)
Mucinous tumors of the ovary are a continuing source of controversy in the field of gynecologic pathology. We examined a series of 171 intestinal-type mucinous tumors of low malignant potential ("borderline" or "atypical proliferative" tumors) to clarify the clinical significance of intraepithelial carcinoma (IECA) and microinvasion (area ≤10 mm 2). The diagnosis of IECA was based on the presence of marked nuclear atypia (grade 3). Stromal microinvasion was classified as low grade and high grade (with nuclear grade 3). IECA was observed in 67 of 171 cases (39.2%). Microinvasion was identified in 31 (18.1%) cases, low grade in 22 (12.9%) cases, and high grade in 9 (5.3%) cases. Follow-up status was known in 144 cases and tumor recurrence was observed in 6 patients (4.2%). The risk factors for recurrence included International Federation of Gynecology and Obstetrics stage ≥IC (P=0.002), microinvasion (P=0.013), age less than 45 years (P=0.032), and IECA (P=0.042). The amount of IECA ≥10% was also associated with the risk of recurrence (P=0.007). Among tumors with microinvasion, there was no significant association between the clinicopathologic variables and recurrence. When considering tumors with stage ≥IC, tumor recurrence was significantly associated with IECA ≥10% (P=0.031) and age less than 45 years (P=0.047). It is important that mucinous tumors of low malignant potential should be staged and be optimally sampled for pathologic examination to document the status of the external surface or peritoneal involvement and to identify the worst degree of epithelial proliferation. Tumor stage ≥IC, IECA ≥10%, microinvasion, and age less than 45 years were the features that were associated with tumor recurrence. The study results also support the use of nuclear grade 3 as the sole criterion of IECA. © 2011 International Society of Gynecological Pathologists.